KARAKTER TOKOH UTAMA DALAM NOVEL SWITCHOVER KARYA MIKEINDIALIMA PADA WATTPAD - Anggraini, Salsabila Putri; Sukardi, Edy (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
Abstract Literature is a craft of human imagination and an entertainment inpirating for any human enjoying it. Wattpad is a digital platfrom which ideas are transmitted to literary novels via the Internet. Character distorts a description of unique characteristics of individuals in various forms of fiction such as novels. The purpose of this study is to examine the character of the utam and transcends the relationship between the background and character of the mikeindialima novel switchover. The method used in this study is a qualitative descriptive method, with the analysis of content. Data obtained by siamk and note, reading is done in capturing the famous mikeindialima novel of 121 chapters, 1.28 million voices and has been read 28.5 million times. Based on research and discussion, the findings found in Anna are some of the characters that presenta good and bad character :1) empathy of 5, 2) a whineness (whiners) as much as 6, 4) as desperate as 5, 5) as paranoid as 6, 6) a high level of 5. And there are also factors that influence the change in Anna's main character in mikeindialima's swithover novel, among which are: internal factors (family matters, past, self-control and love) and external factors (environment).